TD-CDM-OFDM Evolution of TD-SCDMA toward 4G. - Lin Huang; Wenbo Wang; Guiliang Yang; Kan Zheng (IEEE Communications magazine)
TD-SCDMA, which is the "homemade" 3G standard in China, has received considerable attention and is believed to play a critical role in the development of China's mobile communication. Meanwhile, advanced MIMO and OFDM techniques shed light on the feasibility of high-performance 4G broadband systems. We discuss an evolutionary path of TD-SCDMA toward 4G systems in this article, which combines the existing advanced traits in TD-SCDMA with new features for broadband wireless communication systems.